2016
DOI: 10.1002/wcc.416
|View full text |Cite
|
Sign up to set email alerts
|

Drawing the line between adaptation and development: a systematic literature review of planned adaptation in developing countries

Abstract: Climate change adaptation is increasingly considered an urgent priority for policy action. Billions of dollars have been pledged for adaptation finance, with many donor agencies requiring that adaptation is distinct from baseline development. However, practitioners and academics continue to question what adaptation looks like on the ground, especially in a developing country. This study examines the current framing of planned adaptation amidst low socioeconomic development and considers the practical implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 63 publications
0
41
0
1
Order By: Relevance
“…One may conclude, for example, that many of the actions in Quito's adaptation policy may be related to a development deficit. Sherman et al (2016) found that the literature on adaptation in developing countries on the ground offers different interpretations of the integration of adaptation and development. They recognise that this results in different considerations regarding adaptation design, implementation, funding, monitoring and evaluation (Sherman et al 2016).…”
Section: Pilot Application: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One may conclude, for example, that many of the actions in Quito's adaptation policy may be related to a development deficit. Sherman et al (2016) found that the literature on adaptation in developing countries on the ground offers different interpretations of the integration of adaptation and development. They recognise that this results in different considerations regarding adaptation design, implementation, funding, monitoring and evaluation (Sherman et al 2016).…”
Section: Pilot Application: Results and Discussionmentioning
confidence: 99%
“…Sherman et al (2016) found that the literature on adaptation in developing countries on the ground offers different interpretations of the integration of adaptation and development. They recognise that this results in different considerations regarding adaptation design, implementation, funding, monitoring and evaluation (Sherman et al 2016). In this pilot test, any effort puts into providing more adaptive capacity has been considered an indicator of adaptation progress and thereby provide credibility to the process.…”
Section: Pilot Application: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, regardless of whether they are technocratic or “pro‐poor,” there is growing concern that adaptation efforts in the context of development continue to be characterized by time‐bound, donor‐driven projects, which only offer short‐term palliatives to risk (Kates, Travis, & Wilbanks, ; K. O'Brien, ; Pelling, ; Pelling et al, ). They operate within existing social and political contexts, overlooking how these structures themselves can create and perpetuate entrenched inequalities and uneven power relations that are at the root of vulnerability to climate change (Eriksen et al, ; Olsson et al, ; Sherman et al, ; St. Clair, ; Tschakert, van Oort, St. Clair, & LaMadrid, ). Because they avoid disturbing the status quo, these efforts can only facilitate “incremental” adjustments to new risks—and the limits to such incremental adaptation are fast being reached (Kates et al, ; K. O'Brien, ; Pelling, ; Pelling et al, ).…”
Section: Context: Approaches To Social Protection and Parallels With mentioning
confidence: 99%
“…Adaptation can be framed more narrowly as risk management activities in response to climatic drivers, or more widely as ongoing development work that addresses or transforms the underlying socioeconomic drivers of vulnerability, adaptive capacity, and resilience (Lemos et al, 2016;Sherman et al 2016). The complexities surrounding how adaptation is structured as a policy issue, combined with its intrinsic interlinkages with broader development issues -sometimes referred to as the 'fuzziness' of its boundaries -presents challenges for assessing adaptation progress (Robinson, 2017;Sherman et al 2016;Ford et al 2015a;Eakin et al 2014). Making sense of these fuzzy boundaries requires the development of metrics that account for differences in how adaptation activities are framed, without introducing biases into global assessment frameworks that undermine objective, coherent, and consistent analysis .…”
Section: Conceptual Challenges: What To Measure?mentioning
confidence: 99%